Analysis of the differences in the quality of briquettes made from durian peel and young coconut shells as an alternative energy source - Marwanto, Andriana; Mualim, Mualim; Bathari, Rosalia Rina (Poltekkes Kemenkes Bandung, 2026)
Background: Durian peel and young coconut shells are abundant organic waste in Bengkulu City. Up to 80% of coastal waste consists of coconut shells, while durian peel waste can reach 1.5–2 tons/day during harvest season. Poor management contributes to environmental pollution. Converting this waste into biochar briquettes offers a sustainable solution. Objective: To compare the quality of briquettes from durian peel and young coconut shells based on moisture, ash, fixed carbon, volatile matter, and calorific value. Methods: A quasi-experimental (posttest-only) design was used. Briquettes were produced from durian peel and coconut shell charcoal with 5% tapioca binder (300 g per treatment). Results: Coconut shell briquettes showed better quality, with moisture 3.33%, ash 6.33%, fixed carbon 85.96%, volatile matter 4.38%, and calorific value 5922 cal/g. Durian peel briquettes had moisture 2.38%, ash 11.37%, fixed carbon 81.49%, volatile matter 4.77%, and calorific value 5398 cal/g. Coconut shell briquettes met SNI 1/6235/2000 standards, and all parameters differed significantly (p < 0.05). Conclusion: Coconut shell briquettes are more efficient as a solid fuel, while durian peel briquettes remain potential when combined with other biomass. This study supports the use of organic waste as a renewable energy source and contributes to sustainable environmental management in Indonesia.